Forecasting the Brazilian demand for biodiesel using artificial neural networks (Research, Society and Development, 2021)
Biodiesel is a renewable fuel used as an alternative to totally or partially replace petroleum diesel. The mandatory percentage of this biofuel added to fossil diesel in Brazil has constantly been increasing. Predicting the amount of biodiesel that will be demanded in the future is essential to maintain the national surplus balance and assist in the sector decision-making. Artificial neural networks (ANNs) help forecast different types of demands. Therefore, this study uses artificial neural networks to forecast the Brazilian demand for biodiesel. The ANN proposed in this work encompassed data obtained from a non-parametric demand forecasting model based on time series. The non-parametric model considered the trends and seasonality of the data to forecast the demand for biodiesel. One hundred multilayer perceptron networks were modeled with error propagation for two scenarios of Brazilian biodiesel (use of 15% (B15) or 20% (B20) of biodiesel to diesel). All values ​​of R2 greater than 0.99 for the simulated networks and RMSE